Laying Performance and Egg Quality of Hens Supplemented with Sodium Bicarbonate During the Late Laying Period - Yoruk, M.A.; Gul, M.; Hayirli, A.; Karaoglu, M. (International Journal of Poultry Science, 2004)
This study was conducted to determine effects of dietary NaHCO3 supplementation on egg production and egg quality during the late laying period. Hisex Brown layers, 54 wks of age, were blocked according to the cage location and then assigned randomly to receive one of four diets containing 0, 0.1, 0.2, or 0.4% NaHCO3 for 75 d. Each diet was replicated in 6 groups; each consisting of 2 cages containing 10 hens. Feed intake (FI) and egg production (EP) were recorded daily and egg weight (EW) was measured bi-weekly. A sample of 12 eggs from each group were collected randomly every 25 d for specific gravity (SG), shape index (SI), shell stiffness (SS), shell thickness (ST), yolk color (YC), albumen index (AI), yolk index (YI) and Haugh unit (HU). The mortality rate (MR) and feed conversion ratio (FCR) were lower, whereas FI, EP and EW were greater for hens fed the experimental diets than those for hens fed the control diet. Moreover, increasing NaHCO3 level linearly decreased MR and FCR, linearly increased EP and EW and quadratically increased FI. Specific gravity and YI for hens fed the experimental diets were lower than for fed the control diet. The diets did not affect SI, SS, ST, YC, AI and HU. However, SG and YI decreased linearly and AI increased linearly with increasing NaHCO3 level. In conclusion, increasing sodium bicarbonate level positively affected laying performance and altered inner egg quality, but did not improve shell quality, during the late laying period in hens.